Processo de ensino das artes visuais: um caso de estudo - Manta, Argyro Ralli (2018)
In this thesis, we studied (i.e., observed and analysed) the teaching process of visual arts activities (i.e., drawing and painting) in Colégio Oceanus, V. N. Gaia, Portugal, in the context of my 3-month internship. The Art Instructor for the classes of students (i.e., 7 to 10-year-old) that I attended was Ms. Fernanda Santos who followed the projectual methodology like the “Projectual Methodology” of Munari in the design of the artistic education plan (i.e., drawing and painting activities) that she applied.